Conceptualizing the Transnational Regulation of Plastics: Moving Towards a Preventative and Just Agenda for Plastics. Issue 2 (2nd July 2022) - Johnson, Hope; Nay, Zoe; Maguire, Rowena; Barner, Leonie; Payne, Alice; Taboada, Manuela
Abstract: This article categorizes and evaluates how regulatory regimes conceptualize plastics, and how such conceptualizations affect the production, consumption, and disposal of plastics. Taking a doctrinal and policy-oriented approach, it identifies four 'frames' – that is, four distinct and coherent sets of meanings attributed to plastics within transnational regulation – namely, plastics as waste to be managed; a material to be prevented; a good (or waste) to be traded freely; and inputs or outputs in production-consumption systems. Based on this analysis, three significant deficiencies in the transnational regulation of plastics are identified: the failure to frame plastics in terms of environmental justice and human rights issues; insufficient focus on plastics prevention (rather than management); and the role of law in reinforcing its production and consumption.